Language dynamics in the case of an omniscient in the jain literature of Classical period (5th-10th c. Ce) - Glinicka, Małgorzta (Hybris, 2016)
The article “Language Dynamics in the case of an Omniscient” is the study of the idea of an omniscient person on the basis of the classical Jain literature (5th–10th c. CE) in the context of language materiality, human activity and entanglement of a person into karmic bondage.